EFEKTIFITAS DRUM OF WASTEWATER TREATMENT (DOWT) DALAM MEREDUKSI KADAR PHOSPAT DAN NITIRIT LIMBAH CAIR DOMESTIK 2019 - Muh. Fajaruddin Natsir; Makmur Selomo; Ruslan La Ane (Jurnal Nasional Ilmu Kesehatan, 2019)
One source of environmental pollution is wastewater that comes from domestic because it contains high organic compounds and pathogenic microorganisms. This study aims to determine the effectiveness of domestic wastewater treatment with Drum of Wastewater Treatment (DOWT) in terms of Phosphate and Nitrite parameters. This type of experimental research with pretest posttest design by comparing the quality of wastewater before and after treatment. The results showed that the highest reduction in phosphate levels was at 24-hour WTH with measurements at the inlet of 19 mg / L, while at outlets 12.45 mg / L with an efficiency of 34.47%. The highest reduction for Nitrite was at 8 hours WTH with measurement at the inlet of 0.15 mg / L, while at the outlet 0.006 mg / L with an efficiency of 95.97%. Domestic wastewater that is disposed of needs to be treated first because it can pollute the environment.